(3QhVI GdCNHGQ hcfhR GdCSQGQ hfcJ GdBKGQs - (3YeQ Hf SdeGf Hf gGTe Hf CHi GdYTjQI GdeWQi GdNhdGfis
(3ChdgG (B:s
(3GdMeO ddg dGjeKd HGdCacGQ s
(3QJHg GdeDda Ydi CQHYh CLRGAs
(3Hg NQe ef BNQgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B145 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JGQjN (B5526) s
Keywords: (3GdJGQjNs